Effects of the Drying Methods on Physical and Physicochemical Indicators, Antioxidant Activity, and Volatile Flavor Compounds of Bachu Mushrooms - Yanquan LIU; Tian ZHANG; Zhenzhen DING; Wenhan FENG; Yueli WANG; Na XIA (Shipin gongye ke-ji, 2025)
To investigate the effects of different drying methods on the physicochemical properties, antioxidant activity, and volatile flavor compounds of Bactchu mushrooms, three drying methods including hot air drying (HAD), vacuum freeze drying (VFD), and natural drying (ND) were employed. The whiteness, rehydration ratio, soluble protein content, total sugar content, flavonoid content, total phenolic content, DPPH radical scavenging rate, ABTS+radical scavenging rate, and volatile flavor compounds were determined in the dried samples. Results showed that VFD-treated mushrooms exhibited the highest levels of soluble protein, flavonoids and total phenols in both caps (VFDC) and stipes (VFDS) compared with HAD-treated and ND-treated samples, along with superior rehydration ratio and whiteness. VFD also achieved the highest DPPH· and ABTS+· scavenging rates, indicating its ability to preserve nutrients, maintain high antioxidant activity, restore the original structure and prevent browning. Across the three drying methods, 83 volatile flavor compounds were identified, including 16 alcohols, 10 aldehydes, 9 ketones, 7 acids, 13 esters, 19 hydrocarbons, and 9 other compounds. Notably, VFD samples contained the most diverse volatile flavor profiles in both the caps and stipes compared with HAD and ND samples. With the same drying method, the caps of VFD showed a greater variety of compounds than stipes. Conversely, HAD and ND samples exhibited a higher diversity of volatile flavor compounds in the stipes compared to the caps. The combination of radar chart analysis, principal component analysis, and cluster heat-map analysis demonstrated differences in volatile flavor compounds among the six samples. Especially, cluster heat-map could more intuitively distinguish the six samples, which would be used in future research on quality control of dried Bachu mushrooms and exploration of the impact mechanism of drying on flavor compounds. The results of this study would provide a basis and reference for exploring the drying methods of Bachu mushrooms and the effect of drying on mushroom physicochemical indicators, antioxidant activity, and volatile flavor compounds.